1987
DOI: 10.2113/gsecongeo.82.3.600
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and lead isotope studies of stratiform Zn-Pb-Ag deposits, Anvil Range, Yukon; basinal brine exhalation and anoxic bottom-water mixing

Abstract: Five stratiform Zn-Pb-Ag deposits are known in Early Cambrian metapelitic rocks along a curvilinear trend in the Anvil Range, central Yukon. The Anvil Range deposits occur along the southwestern boundary of the Selwyn basin in the stratigraphic transition zone between metapelites of the Mt. Mye unit and calcareous phyllites of the overlying Vangorda unit. The massive sulfides are associated closely with anomalously thick graphitic phyllites, apparently related to a second-order basin. A typical Anvil cycle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…They are stratigraphically controlled, strikingly not be carbonate layers, as would be typical for skarn deposits, but rather by medium-to fine-grained siliciclastic rocks. The geometry of the orebodies conforms to the distribution of sulfide accumulations in first-order, second-order, and third-order sedimentary basins often recognized in sedimentary exhalative sulfide accumulations (Large, 1983;Shanks et al, 1987). The environment of deposition in the large Cambro-Ordovieian basin ranged from platform to shallow marine to deep marine westward and represents the eastern reaches of a deep-marine, first-order basin (Sureda et al, 1986;Martin, 1987;Sureda and Martin, 1990 fides may be more proximal than those at the Esperanza prospect, which consists of only one small ore lens, a point further elaborated below (Fig.…”
Section: Geologic Relationshipsmentioning
confidence: 74%
“…They are stratigraphically controlled, strikingly not be carbonate layers, as would be typical for skarn deposits, but rather by medium-to fine-grained siliciclastic rocks. The geometry of the orebodies conforms to the distribution of sulfide accumulations in first-order, second-order, and third-order sedimentary basins often recognized in sedimentary exhalative sulfide accumulations (Large, 1983;Shanks et al, 1987). The environment of deposition in the large Cambro-Ordovieian basin ranged from platform to shallow marine to deep marine westward and represents the eastern reaches of a deep-marine, first-order basin (Sureda et al, 1986;Martin, 1987;Sureda and Martin, 1990 fides may be more proximal than those at the Esperanza prospect, which consists of only one small ore lens, a point further elaborated below (Fig.…”
Section: Geologic Relationshipsmentioning
confidence: 74%
“…Despite the predictable relationship between the δ 34 S of seawater and hydrothermal sulfi des, Janecky and Shanks (1988) found that sulfur isotope disequilibrium best describes sulfi de and sulfate in seafl oor vent systems, and that the systematic relationship is established at depth in the reaction zone of the seafl oor hydrothermal system. Sulfur isotope studies in the Selwyn Basin (Yukon) by Goodfellow (1987) and Shanks et al (1987) suggested the signifi cance of H 2 S-bearing anoxic bottom waters in determining the isotopic composition of sedimentary-exhalative massive sulfi de deposits. Goodfellow and Jonasson (1984) investigated the sulfur isotope composition of sedimentary pyrite and barite within the Cambrian to Mississippian strata of the Selwyn basin.…”
mentioning
confidence: 99%
“…They used the higher values within the Selwyn basin as evidence that the Selwyn basin had restricted access to the open ocean and that the bottom waters were anoxic and H 2 S-bearing. Shanks et al (1987) extended the Selwyn basin curve farther back into Cambrian time with additional data from the Anvil district. They used data from sedimentary pyrite to defi ne a secular H 2 S curve.…”
mentioning
confidence: 99%
“…GUSTAFSON &? The Canadian Selwyn Basin was an incipient rift basin on Proterozoic (epicratonic) continental crust filled with clastic sediments during Late Proterozoic to late Paleozoic times (GooI) F~LLOW, 1986;SHANKS et al, 1987). The SEDEX deposits of Australia are situated within prominent intracontinental rifts of Middle to Upper Proterozoic age (DuNNET, 1976;WLLLIAMS, 1978).…”
Section: Geotectonic Settingmentioning
confidence: 99%